Evaluation of the Importance of English as a Foreign Language in Elementary Schools in Indonesia - Rahmah, Adinda Aulia (Journal Of Foreign Language Learning and Teaching, 2023)
Currently, the language of instruction in the field of international relations is English. Given the growing number of schools that integrate English in their curricula, this has a strong propensity to rise. The importance of English today is such that it is required in many different spheres of life. According to Panggabean (2015), Indonesia's use of English appears to be highly significant at first glance because it is taught in schools from pre-kindergarten to graduate level and because many universities demand the TOEFL for admission and graduation. However, rather than being used as a tool for communication, English is still seen as a branch of knowledge distinct from other topics and as a foreign tongue. In this context, English in Indonesia refers to English as a Foreign Language (EFL), rather than English as a Second Language (ESL). This demonstrates that English is not prioritized in Indonesia. English is only taught in schools in Indonesia; it is not utilized frequently. Because of this, English is typically taught as a foreign language in Indonesia. In addition to these issues, Indonesian language politics have given English a worsening position with the removal of English classes from the elementary school curriculum in 2013.